1999
DOI: 10.1128/mcb.19.10.6991
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase Clk/Sty Directly Modulates SR Protein Activity: Both Hyper- and Hypophosphorylation Inhibit Splicing

Abstract: The splicing of mammalian mRNA precursors requires both protein phosphorylation and dephosphorylation, likely involving modification of members of the SR protein family of splicing factors. Several kinases have been identified that can phosphorylate SR proteins in vitro, and transfection assays have provided evidence that at least one of these, Clk/Sty, can modulate splicing in vivo. But evidence that a specific kinase can directly affect the splicing activity of SR proteins has been lacking. Here, by using pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
184
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 52 publications
4
184
2
1
Order By: Relevance
“…Another study suggests that splicing factors regulate apoptosis, perhaps by regulating caspase activity (Jiang et al, 1998). It is speculated (Prasad et al, 1999) that the phosphorylation of splicing factors at unique residues facilitates the inactivation of these proteins either by rendering them inactive or by irreversibly complexing them with other proteins of the splicing machinery and thus titrating them out of the splicing reaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study suggests that splicing factors regulate apoptosis, perhaps by regulating caspase activity (Jiang et al, 1998). It is speculated (Prasad et al, 1999) that the phosphorylation of splicing factors at unique residues facilitates the inactivation of these proteins either by rendering them inactive or by irreversibly complexing them with other proteins of the splicing machinery and thus titrating them out of the splicing reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Further dephosphorylation reduces their activity. Similarly, in mammalian cells, both hyper-and hypophosphorylation inhibit the splicing activity of SR proteins (Prasad et al, 1999) and disassemble nuclear speckles (Misteli and Spector, 1996), thus suggesting that intermediate levels of phosphorylation are needed for the functional and structural integrity of these proteins. An alternative interpretation of the differential phosphorylation of PSF, during mitosis and particularly in apoptosis, would be that this protein has functions that are unrelated to splicing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a yeast two-hybrid screen, Colwill and co-workers identified several RNA-binding proteins, all members of the SR family of splicing factors [17]. It was also shown that clk/STY phosphorylates SR proteins and that the phosphorylation status influences their subnuclear localization [17,18]. Clk/STY has been shown to interact and phosphorylate other protein kinases [19] as well as protein phosphatases [20].…”
Section: Introductionmentioning
confidence: 99%